2014
DOI: 10.5312/wjo.v5.i5.597
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative meniscus: Pathogenesis, diagnosis, and treatment options

Abstract: The symptomatic degenerative meniscus continues to be a source of discomfort for a significant number of patients. With vascular penetration of less than one-third of the adult meniscus, healing potential in the setting of chronic degeneration remains low. Continued hoop and shear stresses upon the degenerative meniscus results in gross failure, often in the form of complex tears in the posterior horn and midbody. Patient history and physical examination are critical to determine the true source of pain, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 39 publications
1
75
1
2
Order By: Relevance
“…In general, degenerative tears are associated with increased age and osteoarthritic changes (Berthiaume et al, 2005; Englund, 2008; Greis et al, 2002). Additionally, degenerative tears often have an insidious onset of symptoms without a specific traumatic event initiating injury (Englund, 2008; Howell et al, 2014; Sihvonen et al, 2013). Therefore, to minimize the effects that existing joint degeneration may be playing in the measurements of the present study, patient inclusion criteria were enforced to recruit individuals with an identifiable, traumatic injury and no MRI evidence of cartilage degeneration on the femoral condyles or tibial plateaus of both knees.…”
Section: Discussionmentioning
confidence: 99%
“…In general, degenerative tears are associated with increased age and osteoarthritic changes (Berthiaume et al, 2005; Englund, 2008; Greis et al, 2002). Additionally, degenerative tears often have an insidious onset of symptoms without a specific traumatic event initiating injury (Englund, 2008; Howell et al, 2014; Sihvonen et al, 2013). Therefore, to minimize the effects that existing joint degeneration may be playing in the measurements of the present study, patient inclusion criteria were enforced to recruit individuals with an identifiable, traumatic injury and no MRI evidence of cartilage degeneration on the femoral condyles or tibial plateaus of both knees.…”
Section: Discussionmentioning
confidence: 99%
“…Further trials are needed to better define this subgroup of patients. ►Cite this as: Petersen M eniscal tears can cause pain or locking of the knee joint and prevent those affected from participating in sporting activities, while at the same time reducing their quality of life (1)(2)(3)(4)(5). Radiological studies have shown that osteoarthritis can be a longterm consequence of meniscal injury (2,(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of meniscal injuries occur without adequate trauma (3,4,9). The prevalence of nontraumatic meniscus lesions is 31% according to the Framingham study (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degenerative tears have been suggested to account for about 50% of meniscal tears and are described as “lesions of middle age”, and this pattern of tear was most frequently seen in the posterior horn of the medial meniscus . These injuries tend to impair the load bearing capacity of meniscus and decreases the biomechanical integrity of the tissue, resulting in overloading of cartilage, and ultimately to osteoarthritis (OA) . Hence, early detection of changes in meniscal composition is essential for prevention, or management of meniscal pathologies and control of OA.…”
mentioning
confidence: 99%